Quantitative MRI in myositis patients: comparison with healthy volunteers and radiological visual assessment. Issue 1 (January 2021) - Farrow, M.; Biglands, J.D.; Grainger, A.J.; O'Connor, P.; Hensor, E.M.A.; Ladas, A.; Tanner, S.F.; Emery, P.; Tan, A.L.
Abstract : AIM: To assess whether magnetic resonance imaging (MRI)-based measurements of T2, fat fraction, diffusion tensor imaging, and muscle volume can detect differences between the muscles of myositis patients and healthy controls, and to identify how they compare with semi-quantitative MRI diagnosis. MATERIALS AND METHODS: Sixteen myositis patients and 16 age- and gender-matched healthy controls underwent MRI of their thigh. Quantitative MRI measurements and radiologists' semi-quantitative scores were assessed. Strength was assessed using an isokinetic dynamometer. RESULTS: Fat fraction and T2 values were higher in myositis patients whereas muscle volume was lower compared to healthy controls. There was no difference in diffusion. Muscle strength was lower in myositis patients compared to healthy controls. In a subgroup of eight patients, scored as unaffected by radiologists, T2 values were still significantly higher in myositis patients. CONCLUSIONS: Quantitative MRI measurements can detect differences between myositis patients and healthy controls. Changes in the muscles of myositis patients, undetected by visual, semi-quantitative scoring, can be detected using quantitative T2 measurements. This suggests that MRI T2 values may be useful for the management of myositis patients. Highlights: Quantitative MR can detect differences between myositis and healthy controls. Fat fraction and T2 measurements are higher and muscle volume is lower in myositis. T2 can identify muscle pathology in myositis undetectable by radiologist scoring.